Long-term transition governance and regional innovation cultures: A comparative perspective - Cindy Rentrop; Stefan John; Stefan Böschen; Sebastian Pfotenhauer (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Many regions face pressures to embark on economic, technological, social, and ecological transitions, which often challenge existing regional identities and governance approaches. This paper examines how two regions – the Rhenish Region, affected by the lignite phase-out, and Heilbronn-Franken, confronted with digitalization and global competition in its industrial “Mittelstand” – reconcile long-term transition governance and regional innovation pressures. Despite distinct challenges, both regions share a top-down governance approach, a focus on education and R&D, corporatist actor constellations, dedicated technology implementation strategies, and an emphasis on stability. Within these similarities, socio-economic and cultural differences exist; however, the similarities suggest a mutual learning potential. We propose two levels of reflexivity in long-term governance and argue that these commonalities should be used in national or global strategies for greater inclusivity and effectiveness.